Diamond Smuggling and Taxation in Sub-Saharan Africa - Vocke, Matthias; Oomes, Nienke (Washington, D.C. : International Monetary Fund, 2003)
This paper provides an overview of diamond mining in sub-Saharan African countries, and explores the reasons for substantial differences in their tax rates and fiscal revenues from the sector, which mainly arise from differences in the incentives for smuggling. In a theoretical model, we show that optimal diamond tax rates increase with the degree of competition among diamond buyers, as well as with the corporate share of diamond production, which is confirmed by the data. We then discuss policies to increase revenue, including by enhancing mining productivity, stimulating the exploration of new areas, reducing barriers to entry, and attracting investment into value-adding downstream operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet